Inovasi Pembelajaran Sains Berbasis Bahasa Lokal: Pendekatan THK untuk Meningkatkan Kualitas Pendidikan di Bima - Arwan, Arwan; Taufiqurrahman, M.; Paramita, Shanti; Suryaningsih, Sri (STKIP HARAPAN BIMA, 2025)
This study aims to explore the effectiveness of the use of local languages in science learning based on the Technology, Health, and Culture (THK) approach in Bima. Using qualitative descriptive methods, this study involved grade VII students and teachers in several schools to understand how local languages and THK approaches can improve students' understanding and critical and creative thinking skills. The results showed that using local languages significantly increased students' understanding of scientific concepts, with an increase in comprehension by up to 33%. In addition, integrating the THK approach enriched the learning experience, improving critical thinking skills by 38% and creative thinking by 45%. THK-based learning models have also proven to be effective in improving students' cognitive, affective, and psychomotor learning outcomes. However, there are challenges in terms of technology limitations and teacher training. Therefore, this study recommends increased access to technology and further training for teachers to support the widespread implementation of this model. Overall, this study shows that local language-based approaches and THK can effectively improve science learning quality in culturally rich areas such as Bima